FUZZY SYSTEMS TO SUPPORT INDUSTRIAL ENGINEERING MANAGEMENT - Nunes, Isabel L. (Journal of Applied Engineering Science, 2012)
This paper presents the potentialities of Fuzzy Set Theory to deal with complex, incomplete and/or vague information which is characteristic of some industrial engineering problems. Two systems that were developed to support the activities of industrial engineering managers are presented as examples of the use of this mathematical methodology. Key words: Ergonomics, Work Related Musculoskeletal Disorders, Supply Chain, Resilience, Disturbances
Keywords: Work Related Musculoskeletal Disorders; Ergonomics; Resilience; supply chain; disturbances; Industrial engineering; fuzzy systems